The orally bioavailable GSPT1/2 degrader SJ6986 exhibits in vivo efficacy in acute lymphoblastic leukemia - Chang, Yunchao; Keramatnia, Fatemeh; Ghate, Pankaj S; Nishiguchi, Gisele; Gao, Qingsong; Iacobucci, Ilaria; Yang, Lei; Chepyala, Divyabharathi; Mishra, Ashutosh; High, Anthony A; Goto, Hiroaki; Akahane, Koshi; et al. (Blood, 2023)
Advancing cure rates for high-risk acute lymphoblastic leukemia (ALL) has been limited by the lack of agents that effectively kill leukemic cells, sparing normal hematopoietic tissue. Molecular glues direct the ubiquitin ligase cellular machinery to target neosubstrates for protein degradation. We developed a novel cereblon modulator, SJ6986, that exhibits potent and selective degradation of GSPT1 and GSPT2 and cytotoxic activity against childhood cancer cell lines. Here, we report in vitro and in vivo testing of the activity of this agent in a panel of ALL cell lines and xenografts. SJ6986 exhibited similar cytotoxicity to the previously described GSPT1 degrader CC-90009 in a panel of leukemia cell lines in vitro, resulting in apoptosis and perturbation of cell cycle progression. SJ6986 was more effective than CC-90009 in suppressing leukemic cell growth in vivo, partly attributable to favorable pharmacokinetic properties, and did not significantly impair differentiation of human CD34+ cells ex vivo. Genome-wide CRISPR/Cas9 screening of ALL cell lines treated with SJ6986 confirmed that components of the CRL4CRBN complex, associated adaptors, regulators, and effectors were integral in mediating the action of SJ6986. SJ6986 is a potent, selective, orally bioavailable GSPT1/2 degrader that shows broad antileukemic activity and has potential for clinical development.